2010
DOI: 10.1177/0310057x1003800116
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Residual Neuromuscular Blockade in a Post-Anaesthetic Care Unit

Abstract: We conducted a prospective observational study to assess the incidence of residual neuromuscular blockade (RNMB) in a post-anaesthetic care unit (PACU) of a tertiary hospital. The subjects were 102 patients undergoing general anaesthesia with neuromuscular blockade (NMB). The procedural anaesthetists were unaware of their patients' inclusion in the study, and the choice of muscle relaxant and use of reversal agents were at the anaesthetists' discretion. On arrival to the PACU, the train-of-four ratio was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…In a clinical series of 350 patients undergoing elective surgical procedures at eight public hospitals which can be considered representative of the country because of their geographical location and the number of patients attending annually, the incidence of RNMB was 26%. This percentage is within the range reported in similar studies published in the literature, 1,5,9,17,19 and highlights the dimension of the problem of incomplete neuromuscular recovery in the PACU in our country.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In a clinical series of 350 patients undergoing elective surgical procedures at eight public hospitals which can be considered representative of the country because of their geographical location and the number of patients attending annually, the incidence of RNMB was 26%. This percentage is within the range reported in similar studies published in the literature, 1,5,9,17,19 and highlights the dimension of the problem of incomplete neuromuscular recovery in the PACU in our country.…”
Section: Discussionsupporting
confidence: 87%
“…Although other studies on this topic from different countries have been published, 3,5,17 it is important to have local data because differences do exist between countries and over time. This was an observational trial designed to assess the incidence of RNMB as the primary endpoint but endpoints did not include evaluating the rationale for using neuromuscular block reversal agents or the time since the last dose of neuromuscular blocker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Prolongation of the duration of the neuromuscular blockade increases the risk of clinically relevant paralysis postoperatively and may thus compromise patient safety. 8,[12][13][14][15] To prevent residual neuromuscular block, reliable pharmacological reversal should be achieved before extubation of the trachea. Classically, anesthesiologists have administered cholinesterase inhibitors (for instance, neostigmine) at the end of surgery to antagonize residual effects of neuromuscular-blocking agents.…”
mentioning
confidence: 99%
“…Yet, despite an ever-improving understanding of neuromuscular function and the clinical use of modern neuromuscular monitoring techniques, residual paralysis still remains a significant problem in post anesthesia care units (PACU). 1,2 In fact, Yip et al showed the incidence of patients arriving in the PACU with residual weakness (residual paralysis) to be 31%. Interestingly, in this study the incidence of residual weakness was not significantly lower in patients who received neostigmine, 1 suggesting that we may need to rethink our management of patients who receive neuromuscular blocking agents (NMBAs).…”
Section: Introductionmentioning
confidence: 99%